2011
DOI: 10.1158/1078-0432.ccr-09-3256
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Growth Factor Acts as a Therapeutic Agent and Predictor for Peritoneal Carcinomatosis of Colorectal Cancer

Abstract: Purpose: Here, we aimed to investigate the role of connective tissue growth factor (CTGF) in peritoneal carcinomatosis (PC) associated with colorectal cancer (CRC) and to characterize the underlying mechanism of CTGF mediating adhesion.Experimental Design: A cohort of 136 CRC patient specimens was analyzed in this study. CRC cell lines were used for in vitro adhesion assay and in vivo peritoneal dissemination experiment. Recombinant CTGF protein treatment, transfection of CTGF expression plasmids, and knockdow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…This is the first study indicating that CTGF is an antiadhesion protein in peritoneal metastasis for gastric cancer, and we suggest a therapeutic use for recombinant CTGF in the late stage of this disease. Previous studies in abdominal cancers, such as colorectal cancer, have demonstrated a negative correlation between CTGF expression and cancer progression (survival as well as metastasis) [18,19]. These results are consistent with our findings that CTGF expression is negatively correlated with gastric cancer, which is also an abdominal-origin cancer.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is the first study indicating that CTGF is an antiadhesion protein in peritoneal metastasis for gastric cancer, and we suggest a therapeutic use for recombinant CTGF in the late stage of this disease. Previous studies in abdominal cancers, such as colorectal cancer, have demonstrated a negative correlation between CTGF expression and cancer progression (survival as well as metastasis) [18,19]. These results are consistent with our findings that CTGF expression is negatively correlated with gastric cancer, which is also an abdominal-origin cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Our in vivo results indicate that recombinant CTGF treatment is an effective prevention strategy for peritoneal dissemination as well as an independent prognostic marker for gastric cancer patients. Although previous studies have shown that blocking CTGF using antibodies has shown some promising results in inhibiting pancreatic tumor growth and metastasis in nude mice [28], it was found that the CTGF recombinant protein had a significantly therapeutic effect in advanced colorectal cancer [19]. However, previous studies have reported that CTGF may contribute positively to gastric cancer progression and attenuate adhesion of gastric cancer cells to cultured human peritoneal mesothelial cells [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Chemotherapy is widely used in the clinic and has proved to be effective. Coencapsulation of multiple drugs into nanocapsules may play prominent roles in the treatment of cancers to achieve higher antitumor efficacy and minimize the emergence of resistance.…”
Section: Discussionmentioning
confidence: 99%